Ethanol-Mediated 2D Growth of Cu2O Nanoarchitectures on Nanoporous Cu Templates in Anhydrous Ethanol - Zhenhua Dan; Jiafei Lu; Feng Li; Fengxiang Qin; Hui Chang (Nanomaterials, 2017)
Two types of cupric oxide (Cu2O) nanoarchitectures (nanobelts and nanopetal networks) have been achieved via immersion nanoporous copper (NPC) templates in anhydrous ethanol. NPC templates with different defect densities have been prepared by dealloying amorphous Ti60Cu40 ribbons in a mixture solution of hydrofluoric acid and polyvinylpyrrolidone (PVP) with different ratios of HF/PVP. Both a water molecule reactant acting as OH− reservoir and the ethanol molecule serving as stabilizing or capping reagent for inhibiting the random growth of Cu2Oplayed a role of the formation of 2-dimensional Cu2O nanoarchitectures. Cu2O nanobelts are preferred to form in anhydrous ethanol on the NPC templates from Ti60Cu40 ribbons dealloying in the solution with low HF concentration and small addition of PVP; and Cu2O nanopetals are tended to grow in anhydrous ethanol from the NPC templates from Ti60Cu40 ribbons dealloying in the solution with high HF concentration and large addition of PVP. With increasing the immersion time in anhydrous ethanol, Cu2O nanopetals united together to create porous networks about 300 nm in thickness. The defect sites (i.e., twin boundary) on nanoporous Cu ligaments preferentially served as nucleation sites for Cu2O nanocrystals, and the higher defect density leads to the formation of uniform Cu2O layer. Synergistic effect of initial microstructure of NPC templates and stabilizing agent of ethanol molecule results in different Cu2O nanoarchitectures.